2011
DOI: 10.1002/ijc.26299
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the putative suppressor gene DOK1 by promoter hypermethylation in primary human cancers

Abstract: The DOK1 gene is a putative tumour suppressor gene located on the human chromosome 2p13 which is frequently rearranged in leukemia and other human tumours. We previously reported that the DOK1 gene can be mutated and its expression down-regulated in human malignancies. However, the mechanism underlying DOK1 silencing remains largely unknown. We show here that unscheduled silencing of DOK1 expression through aberrant hypermethylation is a frequent event in a variety of human malignancies. DOK1 was found to be s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 30 publications
6
27
0
Order By: Relevance
“…DOK1 or DOK2 knockout mice show a high susceptibility to developing leukemia and hematological malignancies (19,23,33), as well as lung adenocarcinomas (2). Concomitant with these findings, we showed that DOK1 gene expression was repressed in a large proportion of head and neck cancer (HNC), lung, liver, and gastric cancers, and Burkitt's lymphoma as a result of aberrant hypermethylation of the DOK1 promoter region (1,14,24). These data firmly establish the tumor suppressor properties of DOK1.…”
supporting
confidence: 66%
See 3 more Smart Citations
“…DOK1 or DOK2 knockout mice show a high susceptibility to developing leukemia and hematological malignancies (19,23,33), as well as lung adenocarcinomas (2). Concomitant with these findings, we showed that DOK1 gene expression was repressed in a large proportion of head and neck cancer (HNC), lung, liver, and gastric cancers, and Burkitt's lymphoma as a result of aberrant hypermethylation of the DOK1 promoter region (1,14,24). These data firmly establish the tumor suppressor properties of DOK1.…”
supporting
confidence: 66%
“…HEK293 cells and the HNC cell lines HNC-41 (tonsil), HNC-97 (oral cavity), HNC-124 (oral cavity), and PNS-136 (paranasal sinus) and the colon cancer cell line LoVo were described previously (24). HEK293 cells were transfected using Fugene 6 (Roche Diagnostics) and analyzed 48 h after transfection.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Paradoxically, upon hematopoietic stress, Dok proteins oppose the quiescence of HSC (8,9,48,49). Dok1 and Dok2 dysregulations have been associated with several oncogenic processes (1,6,7,12,(50)(51)(52)(53)(54)(55)(56). Therefore, the impact of chemotherapeutic agents on HSCs may have to be considered to avoid resistance of leukemic stem cells and subsequent relapse.…”
Section: Discussionmentioning
confidence: 99%